1999
DOI: 10.1038/43705
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of nerve growth factor in complex with the ligand-binding domain of the TrkA receptor

Abstract: Nerve growth factor (NGF) is involved in a variety of processes involving signalling, such as cell differentiation and survival, growth cessation and apoptosis of neurons. These events are mediated by NGF as a result of binding to its two cell-surface receptors, TrkA and p75. TrkA is a receptor with tyrosine kinase activity that forms a high-affinity binding site for NGF. Of the five domains comprising its extracellular portion, the immunoglobulin-like domain proximal to the membrane (TrkA-d5 domain) is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
358
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(373 citation statements)
references
References 29 publications
14
358
1
Order By: Relevance
“…Scott et al, 1983;Walsh et al, 1999;Wiesmann et al, 1999;Yeo et al, 1997) . Sequence alignments of NGF, BDNF, and NT-3 (Ibanez et al, 1992;Ibanez et al, 1991;Ibanez et al, 1993;Ilag et al, 1994;Kullander & Ebendal, 1994;Kullander et al, 1997) demonstrate that each neurotrophin possesses seven variable regions that include the same residue positions.…”
Section: Molecular Analysis Of Neurotrophin Structure and Rationale Omentioning
confidence: 99%
See 3 more Smart Citations
“…Scott et al, 1983;Walsh et al, 1999;Wiesmann et al, 1999;Yeo et al, 1997) . Sequence alignments of NGF, BDNF, and NT-3 (Ibanez et al, 1992;Ibanez et al, 1991;Ibanez et al, 1993;Ilag et al, 1994;Kullander & Ebendal, 1994;Kullander et al, 1997) demonstrate that each neurotrophin possesses seven variable regions that include the same residue positions.…”
Section: Molecular Analysis Of Neurotrophin Structure and Rationale Omentioning
confidence: 99%
“…Other substitution and deletion studies confirmed the importance of the N-terminus in specificity (Kullander et al, 1997;Woo et al, 1995;Kahle et al, 1992;Shih et al, 1994). Data from the crystal structure of human recombinant NGF complexed with the TrkA-d5 domains showed that the amino terminal residues 6-9, which were not well-defined in the original NGF crystal structure, adopted a helical conformation upon complex formation with their side chains almost completely buried in the interface (McDonald et al, 1991;Wiesmann et al, 1999) (Fig. 4).…”
Section: The Specificity Patchmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these regions of have been suggested as sites involved in NGF binding based on the X-ray crystal structure of human NGF complexed with human TrkA. 21,22 Targeting Accessible Peptide Segments of a Non-Membrane-Involved Globular Protein…”
Section: Introductionmentioning
confidence: 99%